Implikasi Hukum Tentang Penambahan Dan Perubahan Nama Pada Passport : (Studi Penetapan Nomor : 13/Pdt.P/2022/PN Mtr) - Rizqi Maulana Ibrata; Salim HS; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the procedure for the name change mechanism based on the Court's decision Number: 13/Pdt.P/2022/PN Mtr and the legal implications of the name change in the decision Number: 13/Pdt.P/2022/PN Mtr. This type of research is normative law, with The approach method used is the statutory approach, the conceptual approach, and the analytical approach. The procedure for the name change mechanism is carried out based on the determination of the district court where the applicant is located. The legal implications of a name change are regulated in the provisions of Article 52 of Law Number 23 of 2006 concerning Population Administration which stipulates that a name change is carried out based on the determination of the district court where the applicant is located and Article 24 paragraph 2 of the Minister of Law and Human Rights Number 8 of 2014 concerning the procedure for changing normal passport data.